2013
DOI: 10.1186/1477-7827-11-110
|View full text |Cite
|
Sign up to set email alerts
|

CREBZF expression and hormonal regulation in the mouse uterus

Abstract: BackgroundCREBZF is a member of the mammalian ATF/CREB family of the basic region-leucine zipper (bZIP) transcription factors. Two isoforms of CREBZF have been identified from the alternative usage of initiation codons, SMILE (long isoform of CREBZF) and Zhangfei (short isoform of CREBZF). Until recently, the physiological function of CREBZF in mammalian reproductions has not been reported.MethodsMultiple techniques were performed to investigate the spatiotemporal expression and hormonal regulation of the CREB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(40 reference statements)
4
12
0
Order By: Relevance
“…Our previous studies have reported that 78‐kDa glucose‐regulated protein (GRP78), which is the main regulator of UPR, is significantly increased in implantation site on day 5 in mice (Lin et al, ). ERS‐response‐regulated protein, CREBZF, CREB3 (Luman), and CREBRF (LRF), are also up‐regulated in implantation site in mice (Lan et al, ; Li et al, ; Lin et al, ; Yang, Jin, Lin, et al, ; Yang, Jin, Martyn, et al, ). Therefore, our limited knowledge leads us to speculate that ER stress is involved in regulating embryo implantation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have reported that 78‐kDa glucose‐regulated protein (GRP78), which is the main regulator of UPR, is significantly increased in implantation site on day 5 in mice (Lin et al, ). ERS‐response‐regulated protein, CREBZF, CREB3 (Luman), and CREBRF (LRF), are also up‐regulated in implantation site in mice (Lan et al, ; Li et al, ; Lin et al, ; Yang, Jin, Lin, et al, ; Yang, Jin, Martyn, et al, ). Therefore, our limited knowledge leads us to speculate that ER stress is involved in regulating embryo implantation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CREBZF regulates bone formation and adipocyte differentiation by interacting transcription factors ( Jang et al, 2014 ; Jang et al, 2015 ). Also, recent study indicated that CREBZF is induced by estrogen and closely related to implantation ( Lin et al, 2013 ). However, this study is unclear and lacks the correlation between estrogen and CREBZF expression in endometrium of uterus.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described [ 29 ]. Uterine tissue was immersed in a 4 % formaldehyde solution for 24 h. Then, the tissue was dehydrated gradually in serial concentrations of alcohol and was completely immersed in liquid paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the sections were treated with 3, 3′-diaminobenzidine (DAB) (Sigma-Aldrich Corp., St. Louis, MO, USA) and hematoxylin. For the sections from the negative control group, the ATF6α antibody was replaced with normal rabbit IgG (SC-2763, 1:100, Santa Cruz Biotechnology, Inc., Dallas, Texas, USA) according to our previous report [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation